2017
DOI: 10.1212/wnl.0000000000003457
|View full text |Cite
|
Sign up to set email alerts
|

Risk of fractures after stroke

Abstract: Objective: To determine the risk of fractures after stroke.Methods: Using the Ontario Stroke Registry, we identified a population-based sample of consecutive patients seen in the emergency department or hospitalized with stroke (n 5 23,751) or TIA (n 5 11,240) at any of 11 stroke centers in Ontario, Canada, and discharged alive between July 1, 2003, and March 31, 2012. We compared the risk of low-trauma fractures in patients with stroke vs those with TIA using propensity score methods to adjust for difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
49
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 38 publications
4
49
0
4
Order By: Relevance
“…Analysis of Ontario Stroke Registry (23751 patients were hospitalized with stroke in 2003-2012) [13] also showed that 2-years risk for any low-trauma fracture was lower (HR = 1.32, 95 % CI 1.19-1.46), than for hip fracture (HR = 1.57, 95 % CI 1.35-1.83). In addition, females had greater risk of low-trauma fracture than males (HR = 1.72, 95 % CI 1.53-1.94).…”
Section: B а Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Analysis of Ontario Stroke Registry (23751 patients were hospitalized with stroke in 2003-2012) [13] also showed that 2-years risk for any low-trauma fracture was lower (HR = 1.32, 95 % CI 1.19-1.46), than for hip fracture (HR = 1.57, 95 % CI 1.35-1.83). In addition, females had greater risk of low-trauma fracture than males (HR = 1.72, 95 % CI 1.53-1.94).…”
Section: B а Discussionmentioning
confidence: 99%
“…The risk of osteoporotic fracture increases with post-stroke duration, age of patients (old age), female sex, stroke severity, a positive history of previous fractures or falls, preexisting osteoporosis and concomitant diseases (rheumatoid arthritis, hyperparathyroidism, etc.) [11,13,19]. Despite the prevalent bone loss in the upper extremities in patients with stroke, literature review has demonstrated that hip fracture is the most common osteoporotic fracture [12,13,19].…”
Section: B а Discussionmentioning
confidence: 99%
See 3 more Smart Citations